Programa de gimnasia respiratoria para mejorar la capacidad cardiorrespiratoria de los adultos mayores del grupo del IESS San Martin - Capelo Castillo, Tatiana Maricela (2018)
The research work had designed a program of respiratory gymnastics to improve the cardiorespiratory capacity of the elderly of the gymnastics group of the Ecuadorian Institute of Social Security San Martin. 69% of the patients were women and 31% were men. Based on their personal history, it was determined that 64% had other types of diseases such as breast cancer in women and prostate cancer in men, rheumatoid arthritis, osteoarthritis and osteoporosis, 15% of patients had diabetes, cardiovascular disease were 12% while 9% had thyroid cancer, ovarian cancer in women and prostate cancer in men. The 85.71% had normal values of respiratory rate and 14.29% had a low respiratory rate. 100% of the female and male patients had a normal blood pressure. 81.81% of men did reach the rank of 16 on the Tinetti scale while 18.18% did not reach it; while in women 91.67% of them did reach the maximum score of the scale while 8.33% did not. The respiratory exercise program did not influence body mass or quality of life, however on blood pressure and heart rate if it influences cardiorespiratory fitness. Through the application of the respiratory gymnastics program, the elderly patients of the diurnal gymnastics center of the Ecuadorian Institute of Social Security San Martin reduced physical fatigue, demotivation and psychological affections in the relations of patients with their relatives